2018
DOI: 10.1016/j.euroecorev.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Credit booms, debt overhang and secular stagnation

Abstract: Why do advanced economies fall into prolonged periods of economic stagnation, particularly in the aftermath of credit booms? We present a model of persistent aggregate demand shortage based on strong liquidity preferences of households, in which we incorporate financial imperfections to study the interactions between debt, liquidity and asset prices. We show that financially more deregulated economies are more likely to experience persistent stagnation. In the short run, credit booms can mask this structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…When = 1, we say there is full employment; otherwise, unemployment prevails. It is to be demonstrated, in the next section, that the presence of the lower bound β > 0 on ′( ) is crucial for the existence of unemployment as discussed by Ono (1994Ono ( , 2001 and Illing et al (2018).…”
Section: Environmentmentioning
confidence: 90%
“…When = 1, we say there is full employment; otherwise, unemployment prevails. It is to be demonstrated, in the next section, that the presence of the lower bound β > 0 on ′( ) is crucial for the existence of unemployment as discussed by Ono (1994Ono ( , 2001 and Illing et al (2018).…”
Section: Environmentmentioning
confidence: 90%
“…If τ φ ′ (h t ) that satisfies the first equation in (11) is higher (lower) than the w t determined in the labor market, the firm will hire infinite (zero) labor. Thus, w t is determined so that it satisfies (10) and (11). From (9) and 11, we find…”
Section: The Firmmentioning
confidence: 99%
“…From (10) and 11, real wage w t (= W t /P t ) is constant over time once τ is given, and hence the movement of W t represented by (19) yields…”
Section: The Marketmentioning
confidence: 99%
“…The literature has also shown that certain movements in the economic cycle of certain countries have been caused by the indebtedness promoted by the increase in the price of housing (Illing et al, 2018). According to the International Monetary Fund (IMF), increasing household debt drives economic growth and employment (Lai et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%